Pseudomonas aeruginosa Swarmer Cells Adaptation Toward UVc Radiations - Ghorbal, Salma Kloula Ben; Chourabi, Kalthoum; Maalej, Lobna; Ammar, Aouatef Ben; Ouzari, Hadda-Imene; Hassen, Abdenaceur; Jaafoura, Habib; Chatti, Abdelwaheb (Frontiers in Microbiology, 2019)
Swarming is the most rapid surface motility allowing P. aeruginosa bacteria to rapidly colonize new surfaces. However, Swarming behavior is affected by environmental factors like Ultraviolet irradiation (UVc). UVc radiation is the most commonly applied wastewater disinfection technology, proven to be effective to inactivate microorganisms. However, efficiency against motile bacteria is not yet studied. This study aims to explain the mechanisms of resistance of swarmer Pseudomonas.aeruginosa cells toward UVc exposure. P.aeruginosa liquid cultures were allowed to swarm across a semisolid surface for 18h and directly exposed to UVc radiations. Emergent swarmer colonies, revealed after re-incubation, were selected to study biofilm formation, fatty acid composition and ultratstructure. Our results showed that membrane adaptation to UVc radiations was observed in Pseudomonas cells by an increase in CFA content, confirming the role of cyclopropane in radioresistance of swarmer cells. Furthermore, electron microscopic study confirmed that over production of S-layer is believed to be a protective form adopted by P.aeruginosa swarmer cells to resist after 5 minutes of UVc exposure. Moreover, membrane disintegration is the lethal effect observed after 15 minutes of UVc exposure. In the other hand, study of biofilm production showed an enhancement of biofilm formation, of swarmer cells mainly after 15 minutes of UVc exposure. There results confirmed that swarming process is highly correlated with particular fatty acid composition of P.aeruginosa membrane and that radio-resistance of swarmer cells is highly supported by CFA biosynthesis and S-layer overproduction.